In situ synthesis of water dispersible bovine serum albumin capped gold and silver nanoparticles and their cytocompatibility studies - Murawala, Priyanka; Phadnis, S. M.; Bhonde, Ramesh R.; Bhagavatula L. V. Prasad (Colloids and Surfaces B-Biointerfaces, 2009)
A simple and convenient one step room temperature method is described for the synthesis of bovine serum albumin (BSA) capped gold and silver nanoparticles. BSA reduces silver ions to silver nanoparticles but does not directly reduce gold ions to gold nanoparticles at room temperature and varying pH conditions. However, when silver and gold ions are simultaneously added to BSA, silver ions get reduced to metallic silver first and these in turn reduce gold ions to gold nanoparticles through a galvanic exchange reaction. The so synthesized silver and gold nanoparticles are easily water dispersible and can withstand addition of salt even at high concentrations. It is shown that the capped protein retains its secondary structure and the helicity to a large extent on the nanoparticles surface and that the protein capping makes the nanoparticles cytocompatible. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Ag and Au nanoparticles; Bovine serum albumin; Cytocompatibility; Galvanic exchange reaction; Reductive synthesis

Gellan gum capped silver nanoparticle dispersions and hydrogels: cytotoxicity and in vitro diffusion studies - Dhar, Sheetal; Murawala, Priyanka; Shiras, A.; Pokharkar, V.; Bhagavatula L. V. Prasad (Nanoscale, 2012)
The preparation of highly stable water dispersions of silver nanoparticles using the naturally available gellan gum as a reducing and capping agent is reported. Further, exploiting the gel formation characteristic of gellan gum silver nanoparticle incorporated gels have also been prepared. The optical properties, morphology, zeta potential and long-term stability of the synthesized silver nanoparticles were investigated. The superior stability of the gellan gum-silver nanoparticle dispersions against pH variation and electrolyte addition is revealed. Finally, we studied the cytotoxicity of AgNP dispersions in mouse embryonic fibroblast cells (NIH3T3) and also evaluated the in vitro diffusion of AgNP dispersions/gels across rat skin.

In situ synthesized BSA capped gold nanoparticles: effective carrier of anticancer drug methotrexate to MCF-7 breast cancer cells - Murawala, Priyanka; Tirmale, Amruta; Shiras, Anjali; Bhagavatula L. V. Prasad (Materials Science & Engineering C-Materials For Biological Applications, 2014)
The proficiency of MTX loaded BSA capped gold nanoparticles (Au-BSA-MTX) in inhibiting the proliferation of breast cancer cells MCF-7 as compared to the free drug Methotrexate (MTX) is demonstrated based on MTT and Ki-67 proliferation assays. In addition, DNA ladder gel electrophoresis studies, flow cytometry and TUNEL assay confirmed the induction of apoptosis by MTX and Au-BSA-MTX in MCF-7 cells. Notably, Au-BSA-MTX: was found to have higher cytotoxicity on MCF-7 cells compared with an equivalent dose of free MTX. The enhanced activity is attributed to the preferential uptake of Au-BSA-MTX particles by MCF-7 cells due to the presence of BSA that acts as a source of nutrient and energy to the rapidly proliferating MCF-7 cells. Moreover, the targeting ability of the drug MTX to the over expressed folate receptors on MCF-7 cells also contributes to the enhanced uptake and activity. Taken together, these results unveil that Au-BSA-MTX could be more effective than free drug for cancer treatment. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Apoptosis; Bovine serum albumin; Cancer therapy; Cytotoxicity; Dual active agents; gold nanoparticles